Effects of equivalent beam element on the in-plane shear performance of 3D stochastic fibrous networks. Issue 10 (July 2019) - Long, Kecai; Shi, Liping; Zhong, Yesheng; Luo, Guoquan; Ma, Xiaoliang; Li, Mingwei; He, Xiaodong; Guan, Chunlong
Abstract: The stochastic fibrous network structure in papers, nonwovens, and fibrous tiles have been used and studied widely. The connections in stochastic fibrous networks not only transmit loads between fibers but are also crucial to the mechanical performance of the networks. In this study, a finite element model for three-dimensional (3D) stochastic fibrous networks is built and the connections are treated as equivalent beam elements. Subsequently, the in-plane shear performance of 3D stochastic fibrous networks is investigated. The stress–strain curve and failure analysis obtained from the finite element model agree with the experimental results, thus validating the finite element model. Our simulation suggests that the connections between fibers are crucial on the macromechanical performance of the networks, especially when the damage accumulation is dominated by connections. Flexible connections increase the energy absorption capacity of the material significantly. The diameter of the connecting beam not only affects the strength and modulus of the network, but also changes the elasto-plastic behavior of the network.